FAMILY SURVIVAL OF PRISONERS AS AN IMPACT OF PUNISHMENT - Pradipta, Brilian; Rahayu, Mulyani (Universitas Nusa Cendana, 2025)
This research is motivated by the importance of understanding the impact of punishment on the survival of the inmate's family, especially in Class IIA Ambarawa Correctional Facility. Prisoners who become heads of families often leave a heavy economic and emotional burden on their families. The formulation of this research problem is how the survival of the families of prisoners as a result of punishment. The purpose of the study is to analyze and understand how the families of prisoners survive and adapt during the period of punishment. The method used is descriptive qualitative with a case study approach in Class IIA Ambarawa Prison. Data were collected through interviews with prisoners, families, and prison officers, and supported by relevant documentation. The analysis was conducted using the resilience theory, namely “I Can,” “I Have,” and “I Am,” which describes the ability of individuals and families to overcome social, emotional, and economic pressures due to punishment. The conclusion of this study shows that support from the family, prison, and social environment is very important in building the resilience of families of prisoners. Families who are able to utilize emotional support and develop self-confidence have a greater chance of surviving and rising from the negative impact of punishment. Keywords: Survival; Family of Prisoners; Resilience; Class IIA Ambarawa Correctional Facility; Punishment